ANALISIS PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA PEKERJA PADA PROYEK JALAN TOL SOLO – KERTOSONO DI DONOHUDAN - Bernadus Odi Wismoyo, Amin Wahyudi & Lamidi (Universitas Slamet Riyadi, 2017)
The purpose of this research is to analyze the significance of the influenceoccupational safety and health effects on workers performance. The population is allworkers of PT Wijaya Karya, Waskita Karya, and Nindya Karya KSO Toll Road ProjectSoko - Kertosono in Donohudan which amounts population to 100 workers. Thisresearch uses census method, data collecting technique with interview, questioner andobservation. Data analysis used instrument test, classic assumption test, t test, F test,and coefficient of determination. The result of this research is work safety there issignificant influence to workers performance, occupational health there is significantinfluence to workers performance, occupational health is dominant to workersperformance. Adjusted R2 on multiple linear regression analysis was 87,6%, based on ttest of work safety variable (X1) 0,001 ≤ 0,05 and work health variable (X2) 0,000 ≤ 0,05.Keywords: work safety, occupational health, and workers performance.